Effect of Different Resistance Training Structures on Basic Physical Fitness and Isokinetic Muscular Contraction - Peng Liu; Yeong-Jik Kim; Tae-Beom Seo (Korea Institute of Sport Science, 2023)
PURPOSE This study aimed to investigate the effects of different resistance training structures on basic physical fitness, 1-repetition maximum (1RM), and isokinetic shoulder and knee muscle functions in male college students. METHODS Forty college students were divided into four groups: control group (CG, n=10), compound set training group (CSG, n=10), pyramid set training group (PSG, n=10), and superset training group (SSG, n=10). Excluding CG, each group performed a different resistance exercise method at an intensity of 60~80% 1RM for 60~90 min, three times a week for eight weeks. To compare the effects of resistance training structures, we confirmed body composition, basic physical fitness, 1RM, as well as isokinetic shoulder and knee functions. RESULTS Results indicated that the PSG exhibited the most significant improvement in relative peak torque in isokinetic shoulder and knee testing compared to the other groups. Additionally, all exercise groups positively affected back strength, 40m sprint, and 1RM compared to the CG, although no significant differences were observed among exercise groups. CONCLUSIONS The findings suggest scientific evidence supporting the effectiveness of pyramidal resistance training in improving isokinetic shoulder and knee muscle functions in male college students.